Study on Moisture Content of Kelp in Heat Pump Drying Chamber - WANG Fang; YANG Wen- jia; WANG Peng-hao (Journal of Harbin University of Science and Technology)
Aiming at the problem of long drying time and poor effect of kelp，according to the finite volumemethod，three-dimensional software was used to establish the physical model of heat pump-type kelp drying chamber，and numerical simulation software was used to simulate the kelp moisture content in the material layer of kelp drying chamber. Different drying temperatures，wind speed，grid spacing and other factors were selected to conduct a single-factor simulation study，and the moisture content of kelp was optimized and analyzed based on the comprehensive influence of all factors. It was determined that the drying effect of kelp was optimal under the conditions of 55℃ drying temperature，9 m /s drying airflow velocity and 0. 16 m grid spacing in the drying room. The results provide theoretical guidance for kelp drying.